Seed quality of Cupania vernalis (Sapindaceae) - Oliveira, Luciana Magda de; Nicoletti, Marcos Felipe; Gomes, Juliano Pereira (Revista de Ciências Agroveterinárias, 2010)
Aiming to adapt the tetrazolium test methodology to assess C. vernalis seed quality, seeds from two batches underwent pre-tests looking to select the best method for seeds preconditioning, tetrazolium solution concentration and periods of submersion in the solution. After these factors are defined, the seeds teguments were removed and the embryos were submerged in a 0.1% and 0.5% tetrazolium solution over 18 hours at 25oC. In addition, seeds underwent germination and humidity degree tests. By visual analysis, it was observed that the great majority of embryos subjected to the 0.1% concentration remained faded at the end of the submersion period, besides, only the outcomes from the 0.5% tetrazolium solution were statistically equal to those obtained in the germination test. It leads to the conclusion that the seed tegument extraction and submersion of embryos in the tetrazolium 0.5% solution over 18 hours at 25oC is the appropriate methodology to perform the test in Cupania vernalis seeds.